Basic Concepts of Health Literacy for Equitable Thai Health Systems - คล้อยเอี่ยม, สายชล; สุขประเสริฐ, กมลวรรณ; เจริญเผ่า, ภารุจีร์; คุณารักษ์, ฐานิตา; ไข่ขวัญ, ดวงพร; หวานวาจา, มณฑล (Journal of Health Science of Thailand, 2024)
Health literacy refers to individual knowledge and competencies needed to access, understand, appraise, and apply health information for making health related decisions in order to maintain and improve health for oneself and others. It accumulates throughout the life course through daily activities and social interactions. Health literacy is influenced not only by individual factors, but also organizational structures and availability of resources. Therefore, health systems have direct effects on health literacy among people. With a health literacy friendly health system, people will improve their health literacy and be able to utilize available health related resources. In contrast, there might be an increasing proportion of the population with limited health literacy left behind. The rate of utilization of basic preventive and promotive health services will drop while that of curative services will rise and the health systems cannot handle the situation. This special article presents the basic concepts of health literacy and enabling factors for improving Thai health systems to become health literate and promote health equity. The content covers health literacy as the national agenda, organizational health literacy, health literacy as a modifiable determinant of health, and health literacy as an empowering factor. Furthermore, enabling factors for health literacy friendly health systems are elaborated such as health literacy workforce, health literate organization, health literacy data management, shared decision making in health services, partnerships, technology and innovation for health literacy, financial support and investment, and health literacy leadership. These basic concepts have been drawn from theories and practices from various countries. They will help policy makers, healthcare professionals, and technical health workers to develop equitable health systems to achieve the goal of the national strategic plan.